Peningkatan Kapasitas Penyusunan Dokumen Rencana Kontingensi Banjir dan Kajian Risiko Bencana Desa bagi Destana dan BPBD Kabupaten Muara Enim - Jun Harbi; Hasbi Rizal; Martin Nardi; Agus Fahrurrozi (Altifani Journal: International Journal of Community Engagement, 2026)
Flooding is a dominant disaster threat in Muara Enim Regency, South Sumatra, particularly in villages along the Enim and Lematang Rivers, while most villages still lack adequate flood contingency plans. This community service activity aimed to build participants’ capacity (knowledge and understanding) of developing village flood contingency plans and conducting village disaster risk assessments. The activity was held on 9–10 July 2026 in Muara Enim, involving 100 participants in two sessions: 50 members of the Disaster-Resilient Village (Destana) and 50 staff of the Regional Disaster Management Agency (BPBD). The methods comprised a pre-test, material presentation, interactive discussion and drafting practice, and a post-test; pre- and post-test data were analyzed using a paired sample t-test and Normalized Gain (N-Gain). The results showed that the combined mean score increased from 53.50 to 83.30 (a 55.7% improvement; N-Gain 0.64, moderate category) with a significant difference (p < 0.001). The activity contributed to improving participants’ knowledge; as it employed a single-group design without a comparison group, the results represent post-activity score changes and should be confirmed through continued mentoring and drills.